PERAN BRAND IMAGE DAN WORD OF MOUTH TERHADAP MINAT BELI KONSUMEN DI KEDAI KOPI RADJA: peran brand image memediasi pengaruh word of mouth terhadap minat beli konsumen di kedai kopi radja - Ryan Ermansyah; M Muhajirin (Samalewa: Jurnal Riset & Kajian Manajemen, 2022)
Radja Coffee Shop is one of the business sectors engaged in the culinary field in the city of Bima. To be able to continue to grow, the Radja coffee shop must pay attention to several factors that influence consumer buying interest at the Radja Coffee Shop Kota Bima, including brand image and word of mouth. The purpose of this study was to determine the role of brand image and word of mouth on consumer buying interest at the Radja Coffee Shop, Bima City. This research was conducted on 96 consumers of Radja Coffee Shop. Data obtained through questionnaires distributed to research respondents. Data analysis was performed using multiple linear regression analysis techniques, partial hypothesis testing (t test), simultaneous hypothesis testing (F test), and coefficient of determination test (R2). Based on the results of the study it can be found that brand image and word of mouth have a positive and significant effect on consumer buying interest at Radja Coffee Shop Kota Bima, both partially and simultaneously. The degree of influence of brand image and word of mouth on consumer buying interest at the Radja Coffee Shop Kota Bima is 57%, while the remaining 43% is influenced by variables outside this research model.